Influence of temperatures and precipitation on radial increment of Orlické hory Mts. spruce stands at altitudes over 800 m a.s.l. - M. Rybníček; P. Čermák; T. Kolář; E. Přemyslovská; T. Žid (Journal of Forest Science, 2009)
Research on the influence of temperatures and precipitation on radial increment was carried out in spruce stands over ninety years old in the surroundings of Anenský vrch in the Orlické hory Mts. at altitudes over 800 m above sea level. To model diameter increment in dependence on climatic conditions, the standard tree-ring and correlation analysis together with the analysis of negative pointer years were used. The diameter increment has a statistically significant correlation with temperatures in July of each year in question. The growth of spruce is also affected to a statistically significant degree by precipitation in July of the previous year and by precipitation in February and March of the year in question. The standard tree-ring chronology shows an obvious decrease in radial increments starting at the beginning of the 1970s and ending at the end of the 1980s. The lowest increments were recorded for 1974, 1980, 1984 and 1986. These years with low increments were also confirmed by the analysis of negative pointer years. In the following period there is an increase in increments, with slight decreases in 1996 and 2000, which, however, according to the analysis of negative pointer years do not demonstrate any significant reduction of increments. Another decrease was recorded starting in 2003 and this lasted until the studied period, i.e. 2007. The current condition of spruce stands is certainly the result of more stressors but it appears that with the current air pollution load the climatic conditions are the factor determining the resulting effect of the synergic influence of the stressors on the stands.